WOMEN, AWARENESS AND LAND CONFLICTS: EVIDENCE FROM MAKETE TANZANIA - Samwel Alananga Sanga; Kerbina Joseph Moyo (African Journal on Land Policy and Geospatial Sciences, 2018)
This paper examines the awareness and information access linkages that could be improved to enhance women access to appropriate conflict resolution mechanisms in rural Tanzania. The awareness and access to information indices were constructed and combined with women satisfaction levels based on survey data from 112 women in Makete district. The results suggest that public awareness programmes have the potentials to increasing knowledge on conflict resolution options available to women and enhances the chances that they would report land cases to relevant authorities. Furthermore, the mismatch between land right information delivery through public meetings and village leaders and the need to reduce land conflict in rural areas have caused women to report cases to irrelevant authorities. There is therefore a need for Government, NGOs and international donor community to empower local land tribunals in terms of their capacity to deliver public awareness education among rural communities.